Field trial of a photonics‐based dual‐band fully coherent radar system in a maritime scenario. Issue 3 (1st March 2017) - Scotti, Filippo; Laghezza, Francesco; Onori, Daniel; Bogoni, Antonella
Abstract : This study reports the experimental validation of the first photonics‐based dual‐band radar system in a real maritime scenario, detailing the operation principles as well as the implementation of the demonstrator. The prototype, exploiting photonics for both the generation and the detection of the radar signals, is able to simultaneously handle two radar waveforms in the S ‐band and the X ‐band, ensuring also their reciprocal phase coherence. The proposed system implementation is fully detailed and its characterisation is reported, demonstrating a minimum detectable signal of −124 dBm. Finally, the system is tested in a real scenario, nearby the port of Livorno (Italy), where it successfully detects multiple naval targets, and tracks a cooperative vessel for 8 NM. The obtained results are compared with reference data from automatic identification system and global positioning system recorders, showing a perfect match in terms of range and velocity, both in the S ‐ and X ‐band. Moreover a theoretical analysis of the power budget, considering also the radar cross section in the different frequency bands, is carried out and supported by the experimental observations. Beyond the actual implementation of the proposed system, the outcomes of these tests confirm that the photonics‐based approach can lead new advances in radar architecture, through the development of frequency‐agile photonic transceivers.